Partners of patients with inflammatory bowel disease: how important is their support? - Lahat, Adi (Dove Medical Press, 2014)
BACKGROUND: Chronic inflammatory bowel disease (IBD) causes significant distress for patients and their families. Data assessing the need of these patients for support and sharing with their partners are scarce. The aim of this study was to assess patients’ views regarding sharing of information with their partners. METHODS: Ambulatory IBD patients treated at the Chaim Sheba Medical Center between January 2011 and January 2013 were asked to complete an anonymous questionnaire. Patients who had a stable partner and completed more than 95% of the questionnaire were included. RESULTS: Of 134 patients who agreed to complete the questionnaire, 101 met the inclusion criteria, 53 were men (mean age 45±15 years), and 50% had academic education. Only 42% of patients reported that their partner accompanied them to the doctor. However, 93% shared health problems with their partner, 64% would have liked their partner to receive more medical information, and 70% would like their partner to be more involved. The majority (88%) believed that more partner involvement could help them deal better with the disease, and 70% thought that support groups for partners should be established. No association was found between patients’ demographic data and their answers. Patients who felt that partner involvement could help them to deal with the disease tended to share medical information with their partners and wanted them to be more involved in health care decision-making (P<0.001). CONCLUSION: Most IBD patients in our study wanted their partner to be more involved with their health problems, and believed that greater partner involvement could help them deal better with their disease. Therefore, more attention should be focused on gaining better cooperation from patients’ families.